Limit on Lorentz and CPT violation of the bound neutron using a free precession 3 He/129 Xe comagnetometer - Gemmel, Claudia; Heil, W.; Karpuk, Sergei; Lenz, K.; Sobolev, Yu. G.; Tullney, Kathlynne; Burghoff, M.; Kilian, W.; Knappe-Grüneberg, S.; Müller, W.; Schnabel, A.; Seifert, Frank; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We report on the search for Lorentz-violating sidereal variations of the frequency difference of colocated spin species while the Earth and hence the laboratory reference frame rotates with respect to a relic background field. The comagnetometer used is based on the detection of freely precessing nuclear spins from polarized 3He and 129Xe gas samples using SQUIDs as low-noise magnetic flux detectors. As result we can determine the limit for the equatorial component of the background field interacting with the spin of the bound neutron to be ˜bn⊥<3.7⋅10−32 GeV (95% C.L.).